Non-surgical Periodontal Treatment Restored the Gut Microbiota and Intestinal Barrier in Apolipoprotein E−/− Mice With Periodontitis - Huang, Yuezhen; Liao, Ying; Luo, Binyan; Li, Lili; Zhang, Yangheng; Yan, Fuhua (Frontiers in Cellular and Infection Microbiology, 2020)
Periodontitis has been associated with a variety of systematic diseases via affecting gut microbiota. However the influence of periodontal treatment on intestinal microbiota is not known. Hyperlipidemia can significantly alter gut microbiota structure. It is proposed that the presence of hyperlipidemia can influence the impact of periodontitis on microbiota. This study was conducted to explore the influence of periodontitis and periodontal treatment on the gut microbiota on the basis of hyperlipidemia. Apolipoprotein E−/−（ApoE−/−）mice were ligatured to induced periodontitis and non-surgical periodontal treatment was performed for half of them after 4 weeks of ligation. Microbiota communities in the feces collected at 4, 5, 8weeks after ligation were investigated using next-generation sequencing of 16S rDNA. Bone loss at periodontitis sites were analyzed using micro-computed(Micro-CT) tomography. Morphology and mucosal architecture injury of ileum tissue were observed with hematoxylin-eosin staining. The serum lipid levels were assayed. The results showed that β-diversity index in Ligature-induced-periodontitis group was differed significantly from that of the control group. Significant differences were found in β-diversity between the non-surgical periodontal treatment group and the ligation group. The samples of the non-surgical periodontal treatment group and the control group were clustered together 4 weeks after periodontal treatment. Intestinal villus height and ratio of villus height to crypt depth was found decreased after ligation and restored after non-surgical periodontal treatment. Non-surgical periodontal treatment induced the colonization and prosper of butyrate-producing bacteria Eubacterium, which was absent/not present in the ligation group. We confirmed that periodontitis led to gut microbiota dysbiosis in mice with hyperlipidemia. Non-surgical periodontal treatment had the trend to normalize the gut microbiota and improved the intestinal mucosal barrier impaired by periodontitis in apoE−/− mice.